2023
DOI: 10.3390/nu15132843
|View full text |Cite
|
Sign up to set email alerts
|

Parental Folate Deficiency Inhibits Proliferation and Increases Apoptosis of Neural Stem Cells in Rat Offspring: Aggravating Telomere Attrition as a Potential Mechanism

Abstract: The effect of maternal folate status on the fetal central nervous system (CNS) is well recognized, while evidence is emerging that such an association also exists between fathers and offspring. The biological functions of telomeres and telomerase are also related to neural cell proliferation and apoptosis. The study aimed to investigate the effect of parental folate deficiency on the proliferation and apoptosis of neural stem cells (NSCs) in neonatal offspring and the role of telomeres in this effect. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Our previous study demonstrated reduced folate levels in the neonatal rat offspring's brain tissue, while parental folate deficiency increased Hcy concentrations. Furthermore, the N-N group demonstrated higher folate levels and lower Hcy concentrations in offspring brain tissue than the D-N group [24]. To determine whether parental folate deficiency led to changes in neuronal apoptosis in the fetal brain through intrinsic pathways, we examined the expression of Bcl-2 family proteins (Bcl-2, Bax) via immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated reduced folate levels in the neonatal rat offspring's brain tissue, while parental folate deficiency increased Hcy concentrations. Furthermore, the N-N group demonstrated higher folate levels and lower Hcy concentrations in offspring brain tissue than the D-N group [24]. To determine whether parental folate deficiency led to changes in neuronal apoptosis in the fetal brain through intrinsic pathways, we examined the expression of Bcl-2 family proteins (Bcl-2, Bax) via immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Research we have previously conducted in rats demonstrated that parental folate deficiency decreased folate levels and increased the Hcy levels of the offspring's brain tissue [24]. Increased Hcy in fetal rat brain tissue may lead to decreased recirculation of Hcy to SAM and increased SAH levels, resulting in a decreased methylation capacity, potentially altering the biological function of the central nervous system [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes observed indicate that folate deprivation may harm cerebellar granule cell formation and maintenance. Folate deficiency diets have been linked to cellular deterioration and apoptosis in the cerebrum (Craciunescu et al, 2004; Ren et al, 2023; Zhang et al, 2009). Similar degenerative alterations in the IGC layer were seen in a prior study that investigated the effects of maternal risperidone usage on the histology of the offspring's cerebellar cortex in a rat model (Hanafy, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition limits cell ability to proliferate endlessly [190][191][192]. The enzyme telomerase reverse transcriptase (TERT) prevents critical shortening of telomere length [174].…”
Section: Taurine and Telomere Attritionmentioning
confidence: 99%